Learning with action: Using a didactic strategy in an advanced Pharmacy course at the School of Pharmacy of the University of Costa Rica - León-Salas, Angie (2015)
This study describes the implementation of Project-Based Learning (PBL) with the aim of promoting learning of basic aspects of disease prevention and health promotion to foster the development of skills to increase participation in public health interventions. During 3 weeks, senior pharmacy students at the University of Costa Rica, worked on a project that addressed a health-related problem they considered was affecting their group. Students worked on the development of an intervention and they answered an on-line questionnaire before and after the implementation of PBL. Positive feedback was provided by students and it supports the development of dynamic actions to strength the learning process. We conclude that using PBL allowed the application of actions to support theory. It is necessary to make time and evaluation arrangements in the design of this project in order to continue and improve the strategy.